A PCC DISCOURSE: BODY AND VOICE IN THE KIDNAP-VIDEO - da Costa, Greciely Cristina (2010)
This study analyses the spokesperson figure’s workings (CONEIN, 1981) and the concept of discursive heterogeneity (ORLANDI, 1988), from Discourse Analysis point-of-view. We intend to comprehend the way the subject signifies and constitutes him/herself on the PCC ("First Command of the Capital") kidnap-video. What does he/she forget in order to occupy the spokesperson position? For us, this discursive process has to do with the identification and the differentiation in the relationship between place and subject. Through the spokesperson’s figure, we investigated the identification discourse, which strongly appears through the visual aspects, and the differentiation discourse, which appears through the voice of the Right. Oppositely, two discursive formations are inserted, the Right and the Criminal ones. Two positions occupy the former discursive formation (DF), the defense and the denounce positions. In the later FD, the criminal is signified as being threatening.